Rail tourism in the Pomeranian Voivodship - Otta, Damian (Turystyka i krajoznawstwo, 2021)
Rail tourism and tourism by rail are two issues that are rarely encountered in the literature. This text presents a short definition of both terms, extended by examples of their functioning in the Pomeranian Voivodeship. The railway network of this voivodeship, built mostly under Prussian rule, was quite dense and satisfied the communication needs of the society. World War II, and later the economic changes at the turn of the present century, caused a significant reduction in the railway network. Railway lines, which have survived to this day and used for passenger traffic, allow tourists to reach tourist attractions located in the Pomeranian Voivodeship, and thus foster tourism by rail. On the other hand, lines and structures which ceased to fulfill a communication role, have become sites used in railway tourism. There are also open-air museums and railway museums in the Gdańsk-Pomerania district where tourists can learn about the history of railways in the region. The active spending of time in a railway atmosphere is possible thanks to trolley rides and a narrow-gauge railway.